Assessing the Effect of Packing the Sulcus on Image Quality in Equine Digital Radiography. (16th February 2019) - Rowan, Conor; Puggioni, Antonella; Hoey, Séamus E; O'Leary, John Mark; Kearney, Clodagh; Connolly, Susan E; Skelly, Cliona
Abstract : The requirement to pack the sulcus of the equine foot as an aid to diagnostic interpretation before acquisition of dorsoproximal‐palmarodistal oblique projections is debatable. The purpose of this study was to investigate the benefit of packing the sulcus in the assessment of normal anatomy. 23 cadaver limbs were radiographed in a podoblock (https://www.podoblock.com/products‐page/podoblock/podoblock/) . A non‐packed image (NP) and a packed image (P) of the same foot were acquired. The image quality of P was graded against the reference NP by five observers, where −1=P was superior, 0=no difference between P and NP, and +1=NP was superior. Four anatomical criteria were used: the distal solar margin of the distal phalanx (DP), the vascular channels of DP, the palmar aspect of the distal interphalangeal joint and the articulation of the navicular bone with DP. A total Visual Grading Analysis Score of 0.28 indicates a preference for NP images. Packing was of benefit in only 10.8 per cent of cases. While judicious high‐quality packing may be of benefit in a minority of cases, the routine packing of the sulcus in equine radiography was not found to be of benefit in the assessment of anatomical features in this study.